A Model Based on Noninvasive Markers Predicts Very Low Hepatocellular Carcinoma Risk After Viral Response in Hepatitis C Virus–Advanced Fibrosis. Issue 6 (10th November 2020) - Alonso López, Sonia; Manzano, María Luisa; Gea, Francisco; Gutiérrez, María Luisa; Ahumada, Adriana Maria; Devesa, María José; Olveira, Antonio; Polo, Benjamin Arturo; Márquez, Laura; Fernández, Inmaculada; Cobo, Juan Carlos Ruiz; Rayón, Laura; et al.
Abstract : Background and Aims: Patients with hepatitis C virus (HCV) and advanced fibrosis remain at risk of hepatocellular carcinoma (HCC) after sustained viral response (SVR) and need lifelong surveillance. Because HCC risk is not homogenous and may decrease with fibrosis regression, we aimed to identify patients with low HCC risk based on the prediction of noninvasive markers and its changes after SVR. Approach and Results: This is a multicenter cohort study, including patients with HCV and compensated advanced fibrosis that achieved SVR after direct antivirals. Clinical and transient elastography (TE) data were registered at baseline, 1 year, and 3 years after the end of treatment (EOT). All patients underwent liver ultrasound scan every 6 months. Patients with clinical evaluation 1 year after EOT were eligible. Univariate and multivariate Cox regression analysis were performed, and predictive models were constructed. HCC occurrence rates were evaluated by Kaplan‐Meier. Nine hundred and ninety‐three patients were eligible (56% male; 44% female; median age 62 years), 35 developed HCC (3.9%), and the median follow‐up was 45 months (range 13‐53). Baseline liver stiffness measurement (LSM) (HR 1.040; 95% CI 1.017‐1.064), serum albumin (HR 0.400; 95% CI 0.174‐0.923), 1‐year DeltaLSM (HR 0.993; 95% CI 0.987‐0.998), and 1‐year FIB‐4 score (HR 1.095; 95% CI 1.046‐1.146) were independent factors associated with HCC. The TE‐based HCC risk model predicted 0% of HCC occurrence at 3 years in patients with score 0 (baseline LSM ≤ 17.3 kPa, albumin >4.2 g/dL, and 1‐year DeltaLSM > 25.5%) versus 5.2% in patients with score 1‐3 (Harrell's C 0.779; log‐rank 0.002). An alternative model with FIB‐4 similarly predicted HCC risk. Conclusions: A combination of baseline and dynamic changes in noninvasive markers may help to identify patients with a very low risk of HCC development after SVR.